Leadership and organizational culture towards optimizing employee performance at SMK Negeri 4 Cilegon City - Mukhlisin Mukhlisin; Syaechurodji Syaechurodji; Didit Haryadi (International Journal of Applied Finance and Business Studies, 2023)
Among effective management systems, the importance of human resources is increasing. Employee performance is an essential factor affecting success. In an organization, it is one of the most critical functions of an institution. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study uses an associative descriptive quantitative method with a population of 39 respondents drawn into the sample using non-probability sampling, using the saturated sampling / total sampling method. The data analysis technique uses linear regression with the help of SPSS software version 26. The results of this study indicate that the first hypothesis states that employee performance is influenced by leadership. The second hypothesis states that employee performance is influenced by organizational culture. The third hypothesis, employee performance, is controlled by leadership and corporate culture, which can simultaneously improve employee performance. This research is expected to make a theoretical contribution to the literature in this context, of course, in the context of human resource management.